Relational Dynamics of Treatment Behavior Among Individuals with Tuberculosis in High-Income Countries: A Scoping Review - Arakelyan S; Karat AS; Jones AS; Vidal N; Stagg HR; Darvell M; Horne R; Lipman MC; Kielmann K (Patient Preference and Adherence, 2021)
Stella Arakelyan,1 Aaron S Karat,1,2 Annie SK Jones,3 Nicole Vidal,1 Helen R Stagg,4 Marcia Darvell,5 Robert Horne,3 Marc CI Lipman,5,6,* Karina Kielmann1,* 1Institute for Global Health and Development, Queen Margaret University, Edinburgh, UK; 2TB Centre, London School of Hygiene & Tropical Medicine, London, UK; 3Centre for Behavioural Medicine, Research Department of Practice and Policy, UCL School of Pharmacy, London, UK; 4Usher Institute, University of Edinburgh, Edinburgh, UK; 5UCL Respiratory, Division of Medicine, University College London, London, UK; 6Royal Free London NHS Foundation Trust, London, UK*These authors contributed equally to this workCorrespondence: Karina KielmannQueen Margaret University, Queen Margaret University Way, Edinburgh, EH216UU, UKTel +44 131 474 0000Email KKielmann@qmu.ac.ukAbstract: Although tuberculosis (TB) incidence has significantly declined in high-income, low-incidence (HILI) countries, challenges remain in managing TB in vulnerable populations who may struggle to stay on anti-TB treatment (ATT). Factors associated with non-adherence to ATT are well documented; however, adherence is often narrowly conceived as a fixed binary variable that places emphasis on individual agency and the act of taking medicines, rather than on the demands of being on treatment more broadly. Further, the mechanisms through which documented factors act upon the experience of being on treatment are poorly understood. Adopting a relational approach that emphasizes the embeddedness of individuals within dynamic social, structural, and health systems contexts, this scoping review aims to synthesize qualitative evidence on experiences of being on ATT and mechanisms through which socio-ecological factors influence adherence in HILI countries. Six electronic databases were searched for peer-reviewed literature published in English between January 1990 and May 2020. Additional studies were obtained by searching references of included studies. Narrative synthesis was used to analyze qualitative data extracted from included studies. Of 28 included studies, the majority (86%) reported on health systems factors, followed by personal characteristics (82%), structural influences (61%), social factors (57%), and treatment-related factors (50%). Included studies highlighted three points that underpin a relational approach to ATT behavior: 1) individual motivation and capacity to take ATT is dynamic and intertwined with, rather than separate from, social, health systems, and structural factors; 2) individuals’ pre-existing experiences of health-seeking influence their views on treatment and their ability to commit to long-term regular medicine-taking; and 3) social, cultural, and political contexts play an important role in mediating how specific factors work to support or hinder ATT adherence behavior in different settings. Based on our analysis, we suggest that person-centered clinical management of tuberculosis should 1) acknowledge the ways in which ATT both disrupts and is managed within the everyday lives of individuals with TB; 2) appreciate that individuals’ circumstances and the support and resources they can access may change over the course of treatment; and 3) display sensitivity towards context-specific social and cultural norms affecting individual and collective experiences of being on ATT.Keywords: tuberculosis, adherence, qualitative research, patient-centered care, socio-ecological, low incidence